The Business Model of Hertzian Radio with A Presence on The Internet: From the Perspectives of Administration and Communication - Martins, Henrique Cordeiro; Prata, Nair; Avelar, Kamilla (Advances in Social Sciences Research Journal, 2024)
The business model of the press, in general, and radio, in particular, remained almost unchanged until the 1990s; however, the situation changed with the arrival of the Internet. Therefore, this article aimed to investigate the influence of the antecedents of the business model—value creation, people, strategy, technology, convergence, interaction, and people—of radio stations, taking into account the influence of the Internet on their performance. To this end, a quantitative, descriptive study was carried out with data collected through a survey of Brazilian radio stations with an Internet presence. Data were analyzed using Partial Least Squares Structural Equation Modeling. According to the quantitative data from the survey, the most important antecedents were convergence, strategy, and interaction, and there is a relationship between the business model and the performance of radio stations with an Internet presence.